Dinamika Perkembangan Islam Politik di Nusantara: Dari Masa Tradisional Hingga Indonesia Modern - Yudi Armansyah (Institut Agama Islam Negeri (IAIN) Curup, 2017)
Historically, Indonesia was once a political force that counts the world. It was marked by the birth of political forces during the Hindu Buddhist kingdom until the Islamic sultanate. Ironically, the final phase of the power of political Islam, began to decline since the arrival of colonialism, especially the Dutch colonization that fundamentally colonized in 350 years. But it does not necessarily discourage Islam Politics grow and flourish in the archipelago. Even since Indonesia became independent until it changed into the period of the three Order Lama regimes, the Order Baru and Islamic political reforms remain the barometer of Indonesia's political power. This article is about to unravel the dynamics of the development of political Islam in Indonesia. Where can be classified into two phases, namely the traditional-royal phase, the modern phase. From the results of this study, there are at least two patterns of development of the political power of Islam in Indonesia, which can survive despite real “pressure” from the ruling that is on the political and cultural fields